Microspheres Encapsulating Immunotherapy Agents Target the Tumor-Draining Lymph Node in Pancreatic Ductal Adenocarcinoma. (2nd October 2020) - Han, Booyeon J.; Murphy, Joseph D.; Qin, Shuyang; Ye, Jian; Uccello, Taylor P.; Garrett-Larsen, Jesse; Belt, Brian A.; Prieto, Peter A.; Egilmez, Nejat K.; Lord, Edith M.; Linehan, David C.; Mills, Bradley N.; et al.
ABSTRACT: Introduction: The tumor-draining lymph node (TDLN) plays a role in tumor immunity. Intratumorally administered microspheres (MS) that encapsulate immunomodulatory agents have emerged as a treatment strategy capable of causing profound changes in the tumor microenvironment (TME) and eliciting potent antitumor effects. We hypothesized that local delivery of MS to the TME may also drain to and therefore target the TDLN to initiate antitumor immune responses. Methods: Fluorescent MS were injected into orthotopically implanted murine pancreatic tumors, and tissues were examined by whole-mount microscopy and imaging flow cytometry. The role of the TDLN was investigated for mice treated with intratumoral interleukin-12 (IL-12)-encapsulated MS in combination with stereotactic body radiotherapy (SBRT) by cytokine profile and TDLN ablation. Results: Fluorescent AF-594 MS delivered intratumorally were detected in the tumor, peritumoral lymphatics, and the TDLN 2 h after injection. Phagocytic cells were observed with internalized fluorescent MS. SBRT + IL-12 MS-induced upregulation of Th1 and antitumor factors IL-12, IFN-γ, CXCL10, and granzyme B in the TDLN, and excision of the TDLN partially abrogated treatment efficacy. Conclusions: Our results demonstrate that intratumorally administered MS not only target the TME, but also drain to the TDLN. Furthermore, MS encapsulated with a potent antitumor cytokine, IL-12, induce an antitumor cytokine profile in the TDLN, which is essential for treatment efficacy.